2011
DOI: 10.1111/j.1540-8175.2011.01565.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for the Development of Severe Tricuspid Regurgitation with Anatomically Normal Valve in Patients with Atrial Fibrillation

Abstract: Severe FTR occurs in older patients with chronic AF as a result of marked right atrial and right ventricular dilatation; and enlargement of the tricuspid annulus in the absence of pulmonary hypertension. More importantly, severe FTR leads to increased prevalence of right-sided heart failure underscoring the nonbenign nature of chronic AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 16 publications
4
71
0
Order By: Relevance
“…Yamasaki et al 6 evaluated 11 patients with severe idiopathic TR whose clinical features included chronic AF, RA enlargement, annular dilatation, and diminished fibrillation waves on ECG. Najib et al 7 analyzed 42 patients with severe FTR and AF and found that, in the absence of pulmonary hypertension, FTR occurred in older patients with chronic AF secondary to RA enlargement, altered RV function, and TV annular dilatation, which is consistent with the present study. Similar to the results of Yamasaki et al 6 and Najib et al, 7 we also found .…”
Section: Characterization Of Af-tr In Previous Studiessupporting
confidence: 80%
See 2 more Smart Citations
“…Yamasaki et al 6 evaluated 11 patients with severe idiopathic TR whose clinical features included chronic AF, RA enlargement, annular dilatation, and diminished fibrillation waves on ECG. Najib et al 7 analyzed 42 patients with severe FTR and AF and found that, in the absence of pulmonary hypertension, FTR occurred in older patients with chronic AF secondary to RA enlargement, altered RV function, and TV annular dilatation, which is consistent with the present study. Similar to the results of Yamasaki et al 6 and Najib et al, 7 we also found .…”
Section: Characterization Of Af-tr In Previous Studiessupporting
confidence: 80%
“…Najib et al 7 analyzed 42 patients with severe FTR and AF and found that, in the absence of pulmonary hypertension, FTR occurred in older patients with chronic AF secondary to RA enlargement, altered RV function, and TV annular dilatation, which is consistent with the present study. Similar to the results of Yamasaki et al 6 and Najib et al, 7 we also found . Compared with normal controls, patients with AF-TR had a larger TV annular area and lower ratio of total leaflet length:closure length but comparable tethering of the leaflets.…”
Section: Characterization Of Af-tr In Previous Studiessupporting
confidence: 80%
See 1 more Smart Citation
“…Furthermore, these patients with idiopathic TR were older and atrial fibrillation was more common confirming prior smaller studies. 2,4,5 Approximately two-thirds of patients with severe TR in our study were female with no significant difference in this gender distribution among the 3 classifications of TR. Gender might play a role in determining susceptibility to developing severe TR.…”
Section: Discussionmentioning
confidence: 89%
“…Severe TR may lead to elevated right atrial pressures and/or right atrial dilation, which may contribute to the occurrence of supraventricular arrhythmias 25 26. Indeed, earlier studies have revealed a high prevalence of supraventricular arrhythmias in patients with rTOF,26 27 which may precede death and sustained ventricular tachycardias 16.…”
Section: Discussionmentioning
confidence: 99%